Water Purification and Management - Coca-Prados, José; Gutiérrez-Cervelló, Gemma (NATO Science for Peace and Security Series C: Environmental Security, 2011)
One of the major challenges for many Mediterranean and other countries is finding viable solutions to tackle water shortage. Some of the major water quality constraints derive from the high salinity of groundwater and from pollution sources such as: untreated domestic sewage, fertilizers and pesticides from irrigation drainage, industrial effluents, and solid waste disposal. Wastewater treatment processes involving physico-chemical and biological treatment, chemical oxidation, membrane technologies, along with methods of solids concentration and disposal are of special relevance in dealing with these problems. This volume contains selected lectures presented at the NATO ADVANCED TRAINING COURSE held in Oviedo (November 15-21, 2009) and sponsored by the NATO Science for Peace and Security (SPS) Programme. They cover a variety of topics from wastewater treatment methods to cleaner production strategies, as a careful management of water resources is the basis for sustainable development and to avoid potential security threats. The reader will benefit from a general view of some of the operations involved in wastewater treatment and solid concentration and disposal methods. A proper water reuse and recycling, together with efficient solid disposal, would contribute to a better use of the resources and a sustainable economic growth, particularly in many arid lands of the world.